Novel strategy for efficient screening and construction of host/vector systems to overproduce penicillin acylase in Escherichia coli - Chou, C. P.; Yu, C. C.; Lin, W. J.; Kuo, B. Y.; Wang, W. C. (Biotechnology and Bioengineering, 1999)
A novel and simple method of using penicillin for screening of mutant strains with a high penicillin acylase (PAC) activity was developed. Random mutagenesis was conducted using a PAC-producing strain resistant to 6-aminopenicillanic acid (6-APA) as the parent strain and mutants were screened with penicillin at a high concentration. Results suggest that mutants with a high minimum inhibitory concentration for penicillin (MICpenG) usually overproduce PAC. Both volumetric and specific PAC activities of a mutant, MD7, were significantly higher than those of the parent strain, HBPAC101 harboring pCLL2902. The mutation(s) resulting in the enhanced expression was mapped on the host chromosome rather than the plasmid. In addition, the mutant strain of MD Delta P7, derived by elimination of the harbored plasmid in MD7, was demonstrated to be efficient in production of PAC by using the expression plasmids for which expression of the pac gene is limited by translation. An extremely high specific PAC activity of more than 350 U/L/OD600 was reached upon cultivation of MD Delta P7 harboring pTrcKnPAC2902 in a bioreactor. As such, the strategy is effective in terms of constructing PAC overproducers and improving the process yield for production of PAC. (C) 1999 John Wiley & Sons, Inc.